TEORI SPIRAL, SELEKTIVITAS DAN MATEMATIKAL DALAM AL-QURAN - Taufik Rahman (Kopertais Wilayah III Yogyakarta, 2022)
Alquran is the source of every science and knowledge in this world that absolutely right and undeniable. All knowledge in Alquran, sooner will be known by human in this world.Exploration’s knowlege in Alquran need to be encouraged, especially for us as a moslem’s people to convince more and more, and to make existence of Alquran as a central of science and knowledge.Many west expert that confront a theory, basically that theory has written or spoken in Alquran. Maybe after years, we have just realize, that this theory has already written or spoken in Alquran.Three of that are Spiral, Selectivity and Matematical theory. All these theory, actually has written in Alquran in different way. And what the excited one is, all these theory packed with a wonderful story and elaboration that need special attention to address that this is a theory.